QOLP-25. PERFORMANCE STATUS OF PEDIATRIC PATIENTS WITH CENTRAL NERVOUS SYSTEM TUMORS TREATED IN A TERTIARY CENTER IN MEXICO, A SINGLE-CENTER EXPERIENCE. (12th November 2021) - Madrigal-Avila, Claudia; Ruvalcaba-Sanchez, Rafael; Perez-Bañuelos, Alfonso; Escamilla-Asiain, Gabriela; Ellis, Andrea; Vega-Vega, Lourdes
Abstract: BACKGROUND: Central nervous system (CNS) tumors are the most common solid neoplasms in the pediatric age. Despite this, there are no reports of results focused on the performance status of pediatric patients who are treated in a multidisciplinary setting. OBJECTIVE: Describe the Performance Status of CNS pediatric patients after being treated with a multidisciplinary approach in a tertiary center. METHODS: We review the chart of the pediatric patients at the Teleton Children Oncology Hospital from December 2014 to December 2019. The performance status was evaluated either using ECOG, Karnofsky, or Lansky scores. The multidisciplinary approach at our hospital includes: A Well-Equipped Diagnostic Center, integrated by a CAP-accredited laboratory, a Molecular Biology Unit, and the Imaging Unit, including a high-quality 2 tesla MRI. The surgical equipment comprises a surgical microscope, bipolar coagulation equipment, microsurgical instruments, and craniotomy equipment. For deep biopsies or functional surgery, we use Frame-Based Stereotactic Systems (FBSS) and neuronavigation systems. We provide first-line chemotherapy protocols and have a radiotherapy unit that can start treatment within a week. We have an Intensive Care Unit for oncologic patients with a 93% of overall survival. We provide ludic therapy and cognitive behavioral therapy, as well as emotional support. The Physical Rehabilitation Clinic uses the Bobath concept, proprioceptive and neuromuscular techniques as well as follow-up visits according to needs. RESULTS: Of the 56 patients treated, 35 were evaluated with ECOG/Lansky performance status scale during the last follow up visit, resulting in 74.2% with a fully active performance, able to carry on all pre-disease activities without restriction. CONCLUSION: A multidisciplinary approach is essential in the management of pediatric patients with CNS tumors. Efforts should be aimed at reducing post-surgical morbidity and early rehabilitation to reintegrate patients into society in the long term as we described many of them have an excellent performance status.